Easy marriage, easy divorce : the flaws in Iban traditional adat - Lucy, Sebli (Universiti Malaysia Sarawak, (UNIMAS), 2011)
What is Marriage? Why do people bother to get married if they know that they are going to get divorce in three months or so down the road? Does that have to do with our societal norms and values; or it is simply the notion of 'the right' thing to do at that particular time; or is it because of being human that we allow our heart/emotion to overrule our rational thinking that inevitably lead us to do it? Well, whatever it is, Marriage in its simplest form can be defined as a social contract between two individuals that unites their lives legally, economically and emotionally (Sheri & Bob Stritof 2002). That is to say, when it is a contract everybody has to respect. Divorce however, can be understood as "Dissolution of Marriage" in legal term because the activity cannot come without having a legal marriage. Therefore, under Malaysia Law Reform on Marriage and Divorce Act 1976, no one is allowed to marry another person when a lawful married is still valid.